2015
DOI: 10.1097/mca.0000000000000294
|View full text |Cite
|
Sign up to set email alerts
|

Effects of liposomal prostaglandin E1 on periprocedural myocardial injury in patients with unstable angina undergoing an elective percutaneous coronary intervention

Abstract: Intravenous lipo-PGE1 can reduce the incidence of PMI following elective PCI in patients with unstable angina. The benefit of lipo-PGE1 may be associated with the effects of anti-inflammation as well as improvement in coronary microvascular perfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…The PGE1 group had a reduced incidence of CRIE (RR 0.40 [95%CI 0.43, 0.95]) (Fig. 2) compared with control, as reported in 3 studies, [24,25,27] and there was no evidence for statistical heterogeneity (χ 2  = 2.91, I 2  = 0%, and P heterogeneity  = .878). MACE was reported in 3 studies [24,26,27] and the results suggested that PGE1 reduced the incidence of MACE compared with placebo (0.35 [0.17, 0.70]), with no statistical heterogeneity (χ 2  = 1.24, I 2  = 0%, and P heterogeneity  = .978).…”
Section: Resultsmentioning
confidence: 59%
See 4 more Smart Citations
“…The PGE1 group had a reduced incidence of CRIE (RR 0.40 [95%CI 0.43, 0.95]) (Fig. 2) compared with control, as reported in 3 studies, [24,25,27] and there was no evidence for statistical heterogeneity (χ 2  = 2.91, I 2  = 0%, and P heterogeneity  = .878). MACE was reported in 3 studies [24,26,27] and the results suggested that PGE1 reduced the incidence of MACE compared with placebo (0.35 [0.17, 0.70]), with no statistical heterogeneity (χ 2  = 1.24, I 2  = 0%, and P heterogeneity  = .978).…”
Section: Resultsmentioning
confidence: 59%
“…Of the 6 included studies, 3 involved patients receiving elective PCI, [2527] 1 involved primary PCI, [28] 1 involved elective mitral valve surgery, [29] and 1 involved elective CABG or valve surgery [30] (Table 1). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations